When Do Legal Sanctions Produce Conformity? A Review of the Literature on the Interaction of Perceived Legal Risk with Stakes in Conformity - Rosbough, Christopher P (International Journal of Criminology and Sociology, 2013)
This paper reviews ten published articles on deterrence that address the interaction of stakes in conformity with the perception of legal risk. These articles are classified by types of stakes in conformity examined, such as marriage, education, and employment, and more general types of stakes in conformity, such as social identity. Analysis of evidence suggests that some individuals with low stakes in conformity may be less deterrable by legal sanctions and for those with high stakes in conformity, legal sanctions, such as imprisonment, may increase recidivism. The results, however, continue to show an incongruence between whether and which stakes in conformity act as a consistent deterrent.